A Study on The Role of Primary Health Centres Run by Pune Zilla Parishad in Maharashtra (International Journal of Food and Nutritional Sciences, 2022)
Present research study provides a comprehensive analysis of the role of Primary HealthCenters operated by Pune Zilla Parishad, offering valuable insights for policymakers, healthcarepractitioners, researchers, and stakeholders committed to advancing public health andhealthcare delivery in Pune district